Solomon's Kitten - Jeffries, Sheila (London Simon & Schuster Publishers, 2014)
'This is a special kitten. She has come to heal.' Moments after she is born, tiny kitten Tallulah, with her bright eyes and silver and white fur edged with gold, is whisked away from her father Solomon and dumped in the hedge like rubbish. After a tough start to life, neglected and abandoned, Tallulah eventually finds a new home with the Lee family and forms a special bond with their daughter Tammy. But Tammy has a terrible secret and Tallulah must do all in her power to keep the family safe. Moving, uplifting and inspiring, Solomon's Kitten is the story of a cat who heals a family, and explores the true gift an animal can bring to our lives.
Keywords: Cats -- Human-animal relationships -- Reincarnation